Physiology of lysine permeases in Saccharomycopsis lipolytica. - Beckerich, J M (1978)
Two active lysine transport systems were detected in Saccharomycopsis lipolytica. No excretion of lysine out of the cells could be obtained, even by chasing with L-lysine or by poisoning with sodium azide. The kinetic properties of one of the permeases, the high-affinity lysine permease, were studied in detail. Its Km was 1.91 +/- 0.23 X 10(-5) M. It proved highly specific, the only potent competitive inhibitors being (i) arginine and its analogs L-canavanine and L-ornithine, and (ii) the lysine analogs L-5 aminoethylcysteine and L-4,5-transdehydrolysine. It is suggested that the high-affinity lysine permease is common to L-lysine, L-ornithine, and L-arginine. The other amino acids tested behaved as noncompetitive inhibitors. The variation of uptake during a growth cycle was studied on ammonia-rich, ammonia-poor, and ammonia-free media. In each case, the uptake exhibited a peak in the early exponential growth phase. No new permease activity was detected during the lag phase or the stationary phase. Ammonia ions competitively inhibited the uptake and also decreased the Vmax value.